Imagine heaven : near-death experiences, God's promises, and the exhilarating future that awaits you - Burke, John, 1963- (Baker Books, 2015)
John Burke compares gripping stories of near-death experiences (NDEs) to what Scripture says about our biggest questions of Heaven. The author shows how the common experiences shared by thousands of survivors--including doctors, college professors, bank presidents, people of all ages and cultures, and even blind people--point to the exhilarating picture of Heaven promised in the Bible.